Transcending Life through Romance: Mumbai Tiffinwalas and the Lunch Box - Ghodake, Sangita T. (Advances in Social Sciences Research Journal, 2016)
In a metropolitan city like Mumbai, a city that moves on wheels, a city that gives pan local and pan global experience, often gives feeling of isolation and alienation to her citizens. The absurdity of fast moving life in a metro often leads to universal question, ‘why do we exist?’ The answer lies in optimistic attitude of Mumbai Dabbawalas/ Tiffinwalas whose coping mechanism teaches us how to live and enjoy every single moment of life. They flow with the flow of life by maintaining self respect and dignity. The city plays a role of a protagonist who steers us to ‘never say die’. The Dabbawala or Tiffinwallas have crossed the boundaries of publicity. Right from Prince Charles of Wales, England to a case study of Harward management students have shown their keen interest in the management skills of the semi-literate and non-technical dabbawalas. The present paper is a humble attempt of describing Mumbai city in brief. Life of Mumbai dabbawalas would be described through socio-cultural and financial aspects. Being a teacher of literature, I would like to describe Mumbai and dabbawalas through a Bollywood movie The Lunch Box that has won accolades in national and international film festivals. The movie is a bittersweet romantic comedy in which Mumbai city life is portrayed with her special attribute ‘dabbawala’. The movie depicts a story of two unknown people who get connected through misplacement of tiffin and their romantic letter friendship finally helps them to transcend life in the search of the ‘self’. Their journey started from absurdity and boredom of cactus land that gradually turn into lands of roses and finally transcends them to spiritual quest for ‘know thyself’.